INTEGER PROGRAMMING DENGAN PENDEKATAN METODE BRANCH AND BOUND - NARI, NOLA (Sainstek : Jurnal Sains dan Teknologi, 2013)
The purpose of this study was to determine the allocation of projects to be implemented by the Department of Road Infrastructure Pripinsi West Sumatra in 2005, so the cost minimum. The method used is the method of Branch And Bound together with the simplex method with a solution in the form of binary integer program .. By this method it was found that all the variables that represent each project is worth the cost of the current minimum, so that the entire project could be done with minimum total cost is Rp 17,789,289,600.00. This is in accordance with the reality on the ground that all projects can be realized by the Department of Road Infrastructure West Sumatra province.Key words: branch and bound method, simpleks method, integer biner